Case Report: FGFR2 inhibitor resistance via PIK3CA and CDKN2A/B in an intrahepatic cholangiocarcinoma patient with FGFR2-SH3GLB1 fusion - Ballin, Nadja; Ott, Alexander; Seibel-Kelemen, Olga; Bonzheim, Irina; Nann, Dominik; Beha, Janina; Spahn, Stephan; Singer, Stephan; Ossowski, Stephan; Roggia, Cristiana; Schroeder, Christopher; Bitzer, Michael; et al. (Frontiers in Oncology, 2025)
FGFR2 fusions occur in up to 14% of patients with intrahepatic cholangiocarcinoma (iCCA) and have been considered as therapeutic target for FGFR inhibitors (FGFRi). However, response to targeted treatment may be limited due to the emergence of various resistance mechanisms. We report a case of recurrent iCCA in a 43-year-old patient with a FGFR2 fusion, who was treated with Lenvatinib. Next-generation sequencing (NGS) of tumor-normal DNA and tumor RNA under Lenvatinib treatment confirmed the FGFR2 fusion, however no further molecular resistance mutation was observed. After failure of FGFRi treatment (Lenvatinib and Infigratinib) ten months later, repeated NGS analysis revealed a new gain-of-function mutation in PIK3CA and a homozygous deletion of CDKN2A/B, potentially representing an acquired resistance mechanism. The emerging acquired resistance to FGFR inhibitor treatment has implications for subsequent treatment strategies.